Has there always been underpricing and long-run underperformance? IPOs in Germany before World War I - Christian Schlag; Anja Wodrich (Goethe University Frankfurt, Center for Financial Studies (CFS), 2000)
This paper provides empirical evidence on initial public offerings (IPOs) by investigating the pricing and long-run performance of IPOs using a unique data set collected on the German capital market before World War I. Our findings indicate that underpricing of IPOs has existed, but has significantly decreased over time in our sample. Employing a mixture of distributions approach we also find evidence of price stabilization of IPOs. Concerning long-run performance, investors who bought their shares in the early after-market and held them for more than three years experienced significantly lower returns than the respective industry as a whole..
urn:nbn:de:hebis:30-9760
Keywords: G10; G14; 330; Initial Public Offerings; Underpricing; Long-Run Underperformance; Prize Stabilization; Impact of Changing Stock-Market Regulation and Institution